INFLUENCE OF COORDINATING TECHNIQUES USED BY HEADS OF DEPARTMENT FOR QUALITY ASSURANCE OF BUSINESS EDUCATION PROGRAMME IN COLLEGES OF EDUCATION (NAU Journal of Technology and Vocational Education, 2025)
Coordination is the process of integrating the various units and sub-units in a unified operation towards achieving a common purpose in an organization. The main purpose of the study is to examine the influence of coordinating techniques used by head of departments for quality assurance of business education programme in colleges of education in Kwara State. To facilitate the conduct of the study, two specific purposes, two research questions were raised and answered while one research hypotheses were formulated and tested. The study adopted correlation research design. The population of the study comprised 1,068 made up of 52 lecturers and 1, 016 NCE Business Education students. A random sampling technique was used, and 322 respondents were sampled, made up of 52 lecturers and 270 students, with the use of a research advisor. The instruments used were adapted closed-ended questionnaires. The first questionnaire was tagged Coordinating Techniques Questionnaire (CTQ), and the second one was tagged Quality Assurance of Business Education Programme Questionnaire (QABEPQ). The reliability of the instruments was 0.78 and 0.81, respectively. The collected data were analyzed using mean and standard deviation for research question while Pearson Product Moment Coefficient were used to test the hypothesis at 0.05 level of significance. The findings revealed that there is collaboration among stakeholders as well as conflict resolution among students. The study concluded that stakeholders’ collaboration determines quality of business education programme, and it was recommended among others that stakeholders’ collaboration should be maintained.
Keywords: Coordination Techniques; Quality Assurance; Business Education